Conceptual Analysis of Professional Conscience Among Healthcare Workers in Iran: A Hybrid Analysis. - Dehghani, Ali; Keshavarzi, Abdolkhalegh (Scandinavian Journal of Caring Sciences, 2025)
Background: Professional conscience among healthcare workers is a contextual concept, which depends on various factors. Studies have revealed different meanings, definitions and characteristics for professional conscience. This study was conducted to clarify the concept of professional conscience and identify its characteristics among healthcare workers. Methods: This is a hybrid conceptual analysis, which was conducted in three phases of theoretical, fieldwork and final analysis. In theoretical phase, 22 articles were analysed using a combination of key words 'professional conscience', 'professional conscience in health', 'professional conscience in health workers' and 'health workers' from valid databases. In fieldwork phase, semi‐structured in‐depth interviews were conducted with 15 healthcare workers. In final analysis phase, results of two previous phases were integrated, and a comprehensive definition was presented for the concept of professional conscience. Findings: The six main themes extracted in the theoretical phase included: 'Evidence‐based care', 'ethics reflection in care', 'correct and timely performance', 'professional commitment', 'response to the inner voice' and 'internal personal evaluation'. In fieldwork phase, the seven main themes extracted included: 'nursing as an inner and sacred value', 'human care', 'self‐sacrifice', 'timely response', 'god's supervision in care', 'covenant between oneself and god' and 'being one's own judge'. In final phase, final definition of the concept was presented with combination of results of two previous phases. Conclusions: The findings showed that professional conscience among healthcare workers is a dynamic and multidimensional concept, which consists of dimensions of comprehensive care, sense of commitment and responsibility, divine supervision on performance and self‐evaluation.